Level of Psychological Immunity and its Relationship to Psychological Health among Athletes at Al-Balqa Applied University - Al-Harayzeh , Ja’far (Dirasat: Educational Sciences, 2020)
The purpose of the study is to investigate the level of psychological immunity and its relationship to psychological health among athletes at Al-Balqa Applied University. The sample of the study consisted of (75) male and female students. The researcher adopted a correlation descriptive approach. The findings of the study showed that there is a correlation between the level of psychological immunity and psychological health of athletes at Al-Balqa Applied University. The results showed that there are significant statistical differences in the level of psychological immunity and its relation to the psychological state of athletes at Al-Balqa Applied university due to gender variable in favor of males. The study recommends focusing on the issue of early intervention in order to solve the problems and pressures that affect the gifted students in sports so that they can enjoy sound psychological health.